2011
DOI: 10.1074/jbc.m111.245100
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Degradation Products and Pathways in the Human Lens

Abstract: Vitamin C and its degradation products participate in chemical modifications of proteins in vivo through non-enzymatic glycation (Maillard reaction) and formation of different products called advanced glycation end products. Vitamin C levels are particularly high in selected tissues, such as lens, brain and adrenal gland, and its degradation products can inflict substantial protein damage via formation of advanced glycation end products. However, the pathways of in vivo vitamin C degradation are poorly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 29 publications
0
66
0
Order By: Relevance
“…Nemet and Monnier (25) examined the L-threo-ascorbic acid (ASA, vitamin C) degradation products dehydroascorbic acid (DHA), 2,3-diketogulonic acid 2 The abbreviations used are: AGE, advanced glycation end products; ␣-DC, ␣-dicarbonylcompound;ASA,L-threo-ascorbicacid;DHA,dehydroascorbicacid;2,3-DKG, 2,3-diketogulonicacid(L-threo-2,3-hexodiulosonicacid);3-DT,3-deoxythresosone (4-hydroxy-2-oxobutanal); GO, glyoxal; MGO, methylglyoxal (2-oxopropanal); 3-DG,3-deoxyglucosone(3-deoxy-D-erythro-hexos-2-ulose);OPD,o-phenylenediamine; threosone, 3,4-dihydroxy-2-oxobutanal; 1-DG, 1-deoxyglucosone (1-deoxy-D-erythro-hexo-2,3-diulose); DHA, dehydroascorbic acid; DHAP, dihydroxyacetone phosphate; G3P, glyceraldehyde 3-phosphate; 1-DP, 1-deoxypentosone; 3-DP, 3-deoxypentosone; 3,4-DDP, 3,4-dideoxypentosone (3,4-dideoxypentos-2-ulose);1-DT,1-deoxythresosone(1-hydroxy-2,3-butanedione);Q,quinoxaline;HD patients, patients undergoing hemodialysis; 3-DGal, 3-deoxygalactosone; EtOAc, ethyl acetate; 3,4-DGE, 3,4-dideoxyglucosone-3-ene; MeOH, methanol; CID, collision-induced dissociation; glucosone, D-arabino-hexos-2-ulose; Lederer's glucosone, N…”
mentioning
confidence: 99%
“…Nemet and Monnier (25) examined the L-threo-ascorbic acid (ASA, vitamin C) degradation products dehydroascorbic acid (DHA), 2,3-diketogulonic acid 2 The abbreviations used are: AGE, advanced glycation end products; ␣-DC, ␣-dicarbonylcompound;ASA,L-threo-ascorbicacid;DHA,dehydroascorbicacid;2,3-DKG, 2,3-diketogulonicacid(L-threo-2,3-hexodiulosonicacid);3-DT,3-deoxythresosone (4-hydroxy-2-oxobutanal); GO, glyoxal; MGO, methylglyoxal (2-oxopropanal); 3-DG,3-deoxyglucosone(3-deoxy-D-erythro-hexos-2-ulose);OPD,o-phenylenediamine; threosone, 3,4-dihydroxy-2-oxobutanal; 1-DG, 1-deoxyglucosone (1-deoxy-D-erythro-hexo-2,3-diulose); DHA, dehydroascorbic acid; DHAP, dihydroxyacetone phosphate; G3P, glyceraldehyde 3-phosphate; 1-DP, 1-deoxypentosone; 3-DP, 3-deoxypentosone; 3,4-DDP, 3,4-dideoxypentosone (3,4-dideoxypentos-2-ulose);1-DT,1-deoxythresosone(1-hydroxy-2,3-butanedione);Q,quinoxaline;HD patients, patients undergoing hemodialysis; 3-DGal, 3-deoxygalactosone; EtOAc, ethyl acetate; 3,4-DGE, 3,4-dideoxyglucosone-3-ene; MeOH, methanol; CID, collision-induced dissociation; glucosone, D-arabino-hexos-2-ulose; Lederer's glucosone, N…”
mentioning
confidence: 99%
“…When used as an antioxidant, vitamin C is readily oxidized to DHA. In addition, DHA can be rearranged into additional degradation products, such as 2,3-diketogulonic acid, 3-deoxythreosone, xylosone, and threosone (6). These vitamin C-derived products can covalently modify proteins through nonenzymatic glycation to generate AGEs (7)(8)(9).…”
mentioning
confidence: 99%
“…We did not distinguish between the free and reversibly bound ascorbate degradation products in our assay, unlike in a previous study (16). For DHA-Q, two derivatives were detected, as observed by Henning et al (29).…”
Section: Resultsmentioning
confidence: 66%
“…Therefore, it is reasonable to assume that 3-DT is mainly generated from 2,3-DKG. Moreover, a previous study demonstrated that 3-DT is the dominant free and proteinbound ␣-dicarbonyl in human lenses (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation